Continued improvement of metabolic control in Swedish pediatric diabetes care. Issue 1 (3rd November 2016) - Samuelsson, Ulf; Åkesson, Karin; Peterson, Anette; Hanas, Ragnar; Hanberger, Lena
Abstract : Background: To prospectively investigate if the grand mean HbA1c and the differences in mean HbA1c between centers in Sweden could be reduced, thereby improving care delivered by pediatric diabetes teams. Methods: We used an 18‐month quality improvement collaborative (QIC) together with the Swedish pediatric diabetes quality registry (SWEDIABKIDS). The first program (IQ‐1), started in April 2011 and the second (IQ‐2) in April 2012; together they encompassed 70% of Swedish children and adolescents with diabetes. Results: The proportion of patients in IQ‐1 with a mean HbA1c <7.4% (57 mmol/mol) increased from 26.4% before start to 35.9% at 36 months ( P  < .001), and from 30.2% to 37.2% ( P  < .001) for IQ‐2. Mean HbA1c decreased in both participating and non‐participating (NP) centers in Sweden, thereby indicating an improvement by a spatial spill over effect in NP centers. The grand mean HbA1c decreased by 0.45% (4.9 mmol/mol) during 36 months; at the end of 2014 it was 7.43% (57.7 mmol/mol) ( P  < .001). A linear regression model with the difference in HbA1c before start and second follow‐up as dependent variable showed that QIC participation significantly decreased mean HbA1c both for IQ‐1 and IQ‐2. The proportion of patients with high HbA1c values (>8.7%, 72 mmol/mol) decreased significantly in both QICs, while it increased in the NP group. Conclusions: The grand mean HbA1c has decreased significantly in Sweden from 2010 to 2014, and QICs have contributed significantly to this decrease. There seems to be a spatial spill‐over effect in NP centers.